Investigation of the effects of glycerol addition as a catalyst on the morphology and structural properties of Gd/Er co-doped hydroxyapatite - Mohammed, Bast Ahmed; Ateş, Tankut; Mahmood, Bahroz Kareem; Kareem, Rebaz Obaıd; Keser, Serhat; Bulut, Niyazi; Kaygılı, Omer (Niyazi BULUT, 2024)
This study investigates the effects of increasing amounts of glycerol, ranging from 0 to 16 mL, used in the synthesis on the structural properties of Gd and Er-based hydroxyapatite (HAp). The samples were prepared via a wet chemical route, and their characterizations were carried out using X-ray diffraction (XRD), Fourier transform infrared (FTIR), scanning electron microscopy (SEM), and energy dispersive X-ray (EDX) spectroscopy. The XRD and FTIR results confirmed the formation of the HAp phase in the samples. It was observed that the addition of glycerol at different amounts in the synthesis affected the crystallinity degree and crystallite size. The morphology was almost not affected by the glycerol content as used.
Keywords: Materials Engineering (Other); Malzeme Mühendisliği (Diğer)